Library Policies as Factors Affecting Use of Library by Undergraduate Students of Two Federal Universities in North-Central, Nigeria - Abu, A. A.; Oyedum, D. U.; Raji, R. E.; Abdulhamid, Murjanatu (MiddleBelt Journal of Library and Information Science, 2020)
This study focused on library policies as factors affecting use of library by the undergraduate students of two universities in North-central Nigeria. Libraries are established to enhance the teaching, learning and research activities of the institutions and to achieve this, effective library policies are necessary. Unfortunately, researchers’ investigation disclosed that policies such as overdue are usually not observed in the studied libraries, and this, therefore, course for investigation. The objective of the study is to ascertain the frequency of library use by undergraduate students in the studied universities and investigate the effect of charging and discharging policy as well as finding out the effect of overdue policy on the use of resources. It adopted a descriptive survey design with a population of 11,732 undergraduate students from two federal universities in North-central Nigeria. The study used proportionate stratified random sampling technique to sample 500 undergraduate students. Five hundred copies of questionnaire were distributed and 429 returned; representing a return rate of 86%. The data collected were analysed using descriptive statistics of percentages as well as mean and standard deviation. The decision rule for research questions one through three was based on whether the mean score value was lower than or above the criterion mean value of 2.50 bench-mark. The findings of the study revealed that the use of library resources among students was relatively low. The study also revealed that charging and discharging policy of the library contrarily influences undergraduate students’ use of library, overdue fine policy of the studied libraries is not appropriate. It is concluded that library policies are important variables for effective use of library resources by the undergraduate students in the studied universities. The study therefore also recommended that library management should review some policies such as charges on overdue resources, policy on number of books to be borrowed by users at a time and there is need for university library of studied institutions to migrate to the automated process of discharging information to make it easier for users to access resources.